PENGARUH MERCHANDISING TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN INDOMARET DI KOTA DENPASAR - Kartika Dewi, Ni Luh Made; Sulisyawati, Eka (E-Jurnal Manajemen, 2020)
This study aims to determine the role of customer satisfaction in mediating the influence of merchandising on customer loyalty. This research was conducted in Denpasar City with a total sample of 120 samples. Determination of sample using non probability sampling technique, with purposive sampling method. Methods of collecting data using a questionnaire. The analysis technique used in this study is path analysis. Based on the results of the research conducted, it was found that customer satisfaction had a positive and significant effect in mediating the relationship between the influence of merchandising and the loyalty of Indomaret customers in Denpasar City. Based on the results of the study, it is recommended for Indomaret to pay more attention to merchandising management in order to be more able to increase customer satisfaction to maintain and increase customer loyalty. Keywords : customer loyalty, customer satisfaction, merchandising